ROLE OF THE ENGLISH LANGUAGE IN SOCIETY - Rahimova Dilnora (TADQIQOTLAR, 2026)
Annotation: This article discusses the significant role of the English language in modern society. English has become an essential tool for communication in education, science, business, technology, and cultural exchange. The study examines the spread of English and its impact on social development.